ANALISIS MANAJEMEN ANGGARAN PADA RUMAH SAKIT RUJUKAN DI MASA PANDEMI COVID-19 - Turnip, Helena; Soewondo, Prastuti (Jurnal Ekonomi Kesehatan Indonesia, 2022)
Budget management is a form of accountability for managing cash budgets distributed by the government to hospital agencies so that the budget provided by the central government can be used effectively, efficiently and on target. To examine and explore budget management at hospitals in Indonesia during the COVID-19 pandemic in relation to the budget for the procurement of Personal Protective Equipment (PPE) and infrastructure in hospitals as an effort to overcome the COVID-19 pandemic. PPE (Personal Protective Equipment) is one of the crucial instruments that must be used by all medical personnel in carrying out their duties, this triggers an increase in the PPE procurement budget. Literature Review method by reviewing relevant previous research. Budget management in hospitals has not been categorized as effective and efficient so that more mature planning and budget management are needed for hospitals to manage. As we know that the allocation of funds made to several hospitals in Indonesia was realized by purchasing tools and PPE equipment to add facilities and infrastructure used in tackling the COVID-19.